"We beat the path by walking" Part II: Three construction projects that advanced the learning and credibility of the Indian Alliance. (October 2016) - Patel, Sheela; Bartlett, Sheridan
This paper continues the story of the Indian Alliance (the partnership of SPARC, Mahila Milan and the National Slum Dwellers' Federation), as it designed and built housing with urban poor communities from 1986 to 1995. It focuses on three cases in Mumbai, where communities with precarious housing developed alternatives to resettlement and redevelopment. The housing solutions they developed were the product of negotiation with local authorities and collaboration with the evolving Alliance. The paper documents the collective learning – about the practicalities of construction as well as financing and relationships with local governments – that was instrumental to this work, and that influenced the Alliance's strategies for inclusive community engagement and housing improvements in other locations. These strategies continue to develop and provide valuable lessons that can be applied to the implementation of the new urban Sustainable Development Goal.